Business Cycles and Fiscal Policy in an Open Economy - T. M. Andersen; S. Holden (University of Oslo, Department of Economics, 1998)
Do business cycle fluctuations leave a role and a welfare case for an active stabilization policy by means of fiscal policy instruments? We address this issue in a two-sector open economy model with price-taking firms and imperfect competition in the labour market. Fiscal policies are shown to affect the equilibrium distribution of prices and hence output in the case of both supply (productivity) and demand (preferences) shocks.
Keywords: E32; E63; F41; 330; business cycles; fiscal policy; demand; supply